Vascular sclerosing effects of bleomycin on cutaneous veins: a pharmacopathologic study on experimental animals - Khalid M AlGhamdi; Ashok Kumar; Abdelkader E. Ashour; Ammar C. AL-Rikabi; Abdullah Hasan AlOmrani; Shaik Shaffi Ahamed (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Varicose veins and the complications of venous disease are common disorders in humans. Objective: To study the effects of bleomycin as a potential new sclerosing agent and its adverse events in treating varicose veins. Methods: Bleomycin-loaded liposomes 0.1ml was injected in the dorsal ear veins of white New Zealand rabbits. Sodium tetradecyl sulfate was used as a positive control. Normal saline was used as negative control. The blood vessels of the treated ears were photographed before and at one hour and two, eight and 45 days after treatment. Biopsies from the treated areas were obtained for histological examination. Blood samples were collected to determine any possible toxicity. Results: Bleomycin by itself was ineffective; therefore, liposomes were used as a vector to deliver bleomycin to the vein lumen. Subsequently, bleomycin started showing its sclerosing effects. Toxicity monitoring showed no apparent hematologic, pulmonary, hepatic or renal toxicities. This study revealed that bleomycin induced vasculitis, which led to vascular occlusion, which was observed on day 1 and day 8. No bleomycin-related injury was noted by histopathological examination of lung sections. The calculation of the lung/body weight coefficient indicated that edema was present in the experimental groups compared with the negative and positive controls. Study limitations: Relatively small number of experimental animals used. Conclusions: This study showed that bleomycin-loaded liposomes were able to induce vasculitis and vascular occlusion without any toxicity or complications. It might be useful, hence, to treat patients suffering from Varicose veins and other ectatic vascular diseases with this agent.